Nocturnal Hypoxemia in Respiratory Medicine: Pathophysiology, Measurement, and Association with Outcomes - Hajipour, Mohammadreza; Labarca, Gonzalo; Ayas, Najib; Azarbarzin, Ali (Seminars in Respiratory and Critical Care Medicine, 2025)
Nocturnal hypoxemia is a prevalent feature of various respiratory diseases, significantly impacting patient outcomes and therapeutic strategies. Oximetry, a noninvasive and widely accessible tool, enables the measurement of nocturnal hypoxemia through oxyhemoglobin saturation (SpO2)-derived metrics such as the oxygen desaturation index, percentage of sleep time with SpO2 below 90%, mean SpO2, and measures of the area under the desaturation curve (e.g., sleep apnea-specific hypoxic burden). While these metrics are well established in obstructive sleep apnea (OSA), their application in other respiratory conditions, including chronic obstructive pulmonary disease, pulmonary hypertension, obesity hypoventilation syndrome, heart failure, neuromuscular disorders, pregnancy, and high-altitude residents, remains an area of active investigation. This review explores the pathophysiology of hypoxemia in these conditions and evaluates the role of SpO2-derived metrics in risk stratification beyond OSA. We also discuss the challenges of interpreting SpO2 data, particularly the difficulty differentiating disease-related hypoxemia from comorbid OSA. Additionally, we examine the limitations of oximetry, including sensor inaccuracies, motion artifacts, and skin pigmentation. Finally, we emphasize the need for further research to standardize these metrics across diverse conditions and advocate for their integration into clinical practice to enhance patient management and outcomes.
Keywords: nocturnal hypoxemia; pulse oximetry; respiratory disease; hypoxic burden; OSA